Uncoupling protein 2 prevents ischaemia reperfusion injury through the regulation ROS/NF-κB signalling in mice. (1st January 2019) - Zhang, Yaolei; Guo, Xin; Li, Ting; Feng, Yaxing; Li, Wei; Zhu, Xiaoyan; Gu, Rui; Zhou, Longfu
Abstract: Background and objective: Renal ischaemia reperfusion injury (IRI), characterized by excessive cell apoptosis and inflammation, remains a clinical challenge. Mitochondrial membrane potential is related to apoptosis and inflammation of IRI. Previous studies have indicated that uncoupling protein 2 (UCP2) and its receptors play an important role in inflammation, apoptosis and injuries, especially in oxidative stress injury. However, the underlying mechanisms of UCP2 in IRI are still not fully understood. Methods and results: In the present study, male C57 mice were randomly divided into three groups:sham, IR, and UCP2 -/- +IR. The IRI model was established by removing the right kidney and clamping the left kidney for 45 min followed by reperfusion. Blood urea nitrogen (BUN) and creatinine were higher in UCP2 -/- +IR mouse serum than in IR mouse serum. In addition, relative to the IR group, UCP2 -/- +IR mouse renal cells had increased reactive oxygen species (ROS) production, aggravating tissue damage. We examined changes in the NFκB pathway and found that after UCP2 knockdown, IκB and IKK phosphorylation increased, and nuclear NFκB increased, which stimulated inflammation. Moreover, there was an increase in apoptosis in the UCP2 -/- +IR group. Conclusion: UCP2 can prevent IRI in C57 mice. Mechanistically, UCP2 may decrease ROS expression, NFκB activation and caspase-3 cleavage, rendering UCP2 a potential therapeutic target against IRI.